O efeito da orientação parental no desenvolvimento motor de bebês - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Before babies are able to explore the environment on their own, it is the parents who promote these stimuli. Thus, the study aimed to analyze the impact of parental guidance on stimuli for better motor development of infants. This is a quasi-experimental, descriptive study in which 44 babies and their respective parents participated. For data collection, a questionnaire was applied with the baby and mother data. To evaluate motor development, the Alberta Infant Motor Scale (AIMS) was used. After the evaluation, the parents were informed about the result of their baby’s motor development and were instructed about the stimuli to be performed daily. Parents received a folder with all the guidelines. After an average of 2 months the babies were reevaluated. Data analysis was performed using the SPSS software (version 20,0). For investigation of the effect size, it was calculated or partial eta squared. 61,4% of the sample babies were male, with a mean age of 3,35 ± 1,86 months. In the first evaluation 63,6% of the babies showed, by AIMS evaluation, suspicion of delayed motor development, and in the second evaluation 72,7% of the babies were in the “typical development” category. The effect size of the raw score between the first and second evaluation was 0,742. Parental guidance was effective in promotion good motor development of infants in the age group studied.
The effect of parental guidance on the motor development of babies
Keywords: Motor development; Parental guidance; Motor evaluation; Desenvolvimento motor; Orientação parental; Orientação parental; Avaliação motora; CNPQ::CIENCIAS DA SAUDE